Inhibition of multidrug resistance-associated protein 2 (MRP2) activity by the contraceptive nomegestrol acetate in HepG2 and Caco-2 cells - Tocchetti, Guillermo Nicolás (2018)
Multidrug resistance-associated protein 2 (MRP2) plays a key role in hepatic and intestinal disposition of endo- and xenobiotics. Several therapeutic agents modulate MRP2 activity resulting in pharmacological interactions. Nomegestrol acetate (NMGA) is a progestogen increasingly used in contraceptive formulations. The aim of this work was to evaluate the effect of NMGA on MRP2 activity in HepG2 and Caco-2 cells as models of human hepatocytes and enterocytes, respectively. NMGA (5, 50 and 500 nM; 48 h) decreased MRP2-mediated transport of 2,4-dinitrophenyl-S-glutathione in HepG2 cells, with no effect on MRP2 protein expression. Acute exposure (1 h) to the same concentrations of NMGA failed to affect MRP2 activity, ruling out an inhibitory action directly induced by the drug. In contrast, acute incubation with a lysate of HepG2 cells pre-treated with NMGA, containing potential metabolites, reproduced MRP2 inhibition. Preincubation of lysates with sulfatase but not with β-glucuronidase abolished the inhibitory action, strongly suggesting participation of NMGA sulfated derivatives. Western blot studies in plasma vs. intracellular membrane fractions ruled out internalization of MRP2 to be responsible for the impairment of transport activity. MRP2-mediated transport of 5(6)-carboxy-2′,7′-dichlorofluorescein was not affected in Caco-2 cells incubated for 48 h with either 5, 50 or 500 nM NMGA. Conversely, acute exposure (1 h) of Caco-2 cells to NMGA-treated HepG2 lysates decreased MRP2 activity, being this effect also prevented by pre-treatment of the lysates with sulfatase. Taken together, these findings demonstrate an inhibitory effect of NMGA sulfated metabolites on hepatic and intestinal MRP2 function. Extrapolated to the in vivo situation, they suggest the possibility of pharmacological interactions with coadministered drugs.